2016
DOI: 10.3171/2015.8.jns151140
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Knife radiosurgery in the treatment of abducens nerve schwannomas: a retrospective study

Abstract: OBJECTIVE Of the intracranial schwannomas, those arising from the vestibular nerves are the most common. Abducens nerve (AN) schwannomas are very rare, and there is limited literature on their optimal management. Therapeutic options include surgery and/or stereotactic radiosurgery. The aim of this study was to evaluate the role of Gamma Knife radiosurgery (GKRS) in these sixth cranial nerve (CN) schwannomas. METHODS The authors performed a retrospective analysis of patients who had undergone GKRS for intracran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…In this study, we report actuarial tumor control rates of 96% at 1 year and 86% at 10 years, which are comparable with the 92%-100% control rates described in previous studies. 7,8,[10][11][12][13]15,17,18 These results also mirror some reports from prior studies pertaining to other cranial nerve schwannomas, most commonly those originating from the vestibular (10-year control of 92%), 3 trigeminal (10year control of 95%), 1 facial (5-year control of 90%), 6 and jugular foramen (10-year control of 82%) 5 nerves. This suggests that schwannoma radiosensitivity is an intrinsic characteristic of this tumor type and may be less related to the nerve of origin.…”
Section: Tumor Controlsupporting
confidence: 86%
See 4 more Smart Citations
“…In this study, we report actuarial tumor control rates of 96% at 1 year and 86% at 10 years, which are comparable with the 92%-100% control rates described in previous studies. 7,8,[10][11][12][13]15,17,18 These results also mirror some reports from prior studies pertaining to other cranial nerve schwannomas, most commonly those originating from the vestibular (10-year control of 92%), 3 trigeminal (10year control of 95%), 1 facial (5-year control of 90%), 6 and jugular foramen (10-year control of 82%) 5 nerves. This suggests that schwannoma radiosensitivity is an intrinsic characteristic of this tumor type and may be less related to the nerve of origin.…”
Section: Tumor Controlsupporting
confidence: 86%
“…Nine studies published between 2002 and 2017 described a limited number of tumors managed by SRS, ranging from 1 to 6 cases per study. 7,8,[10][11][12][13]15,17,18 Eight of these studies reported long-term tumor control rates of 100%, while 1 study described a The rate of worsening symptoms was null in most studies, with one study describing 6% of neurological deterioration due to tumor expansion and another study identifying 3 instances of transient diplopia and 1 case of visual deterioration due to orbital tumor extension (Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations